Soliton Generation in Negative Thermal Expansion Materials - Curry, Erin B.; Lyszak, Kaitlin; Sheets, Donal; Occhialini, Connor A.; Rozman, Michael G.; Hancock, Jason N. (Frontiers in Materials, 2021)
Strain solitons have been observed statically in several 2D materials \cite{Alden2013,Edelberg2020} and dynamically in substrate materials using ultrafast laser pulses\cite{Hao2001,Wright2001,Peronne2006,Matsuda2015,Peronne2017}. The latter case relies on lattice relaxation in response to ultrafast heating in a light-absorbing transducer material, a process which is sensitive to the thermal expansion coefficient. Here we consider an unusual case where the sign of the thermal expansion coefficient is negative, a scenario which is experimentally feasible in light of rapid and recent advances in the discovery of negative thermal expansion materials\cite{Sleight1998,Miller2009,Lind2012,Takenaka2012,Dove2016,Attfield2018}. We present numerical solutions to a nonlinear differential equation which has been repeatedly demonstrated to quantitatively model experimental data and discuss the salient results using realistic parameters for material linear and nonlinear elasticity. The solitons that emerge from the initial value problem with negative and positive thermal expansion are qualitatively different in several ways. The new case of negative thermal expansion gives rise to a nearly-periodic soliton train with chirped profile and free of an isolated shock front. We suggest this unanticipated result may be realized experimentally and assess the potential for certain applications of this generic effect.